Mobile Student Verification System for Major Examination (S-VEC) - Aziman, Abdullah; Ong, Lai Chin (Universiti Malaysia Pahang, 2008)
Mobile computing is one of the emerging fields in computer science. Its concept is to utilize the power of computational in a mobile device such as mobile phone and pocket PC. This research project has been carried out to investigate the possibility of using mobile application in simplifying and automated processes in invigilating examination. We have collected feedback from invigilators regarding the issue towards process improvement in invigilating processes. The positive feedback from the survey have lead this proposal to the prototype development of the mobile application. However, after the application was tested in a real environment (examination), we found that the prototype needs more improvement especially in the part of searching the candidates' information. We also used a single XML data to store text data and image data of students. The test parameter of the prototype is search duration for each candidate based on time stamp recorded in XML data file.